Sesamin mitigates lead-induced behavioral deficits in male rats: The role of oxidative stress - Shahab Ghaderi; Masome Rashno; Alireza Sarkaki; Seyed Esmaeil Khoshnam (Brain Research Bulletin, 2024)
Lead (Pb) is a well-known toxic pollutant that has negative effects on behavioral functions. Sesamin, a phytonutrient of the lignan class, has shown neuroprotective effects in various neurological disorder models. The present study was undertaken to evaluate the putative protective effects of sesamin against Pb-induced behavioral deficits and to identify the role of oxidative stress in male rats. The rats were exposed to 500 ppm of Pb acetate in their drinking water and simultaneously treated orally with sesamin at a dose of 30 mg/kg/day for eight consecutive weeks. Standard behavioral paradigms were used to assess the behavioral functions of the animals during the eighth week of the study. Subsequently, oxidative stress factors were evaluated in both the cerebral cortex and hippocampal regions of the rats. The results of this study showed that Pb exposure triggered anxiety-/depression-like behaviors and impaired object recognition memory, but locomotor activity was indistinguishable from the normal control rats. These behavioral deficiencies were associated with suppressed enzymatic and non-enzymatic antioxidant levels, and enhanced lipid peroxidation in the investigated brain regions. Notably, correlations were detected between behavioral deficits and oxidative stress generation in the Pb-exposed rats. Interestingly, sesamin treatment mitigated anxio-depressive-like behaviors, ameliorated object recognition memory impairment, and modulated oxidative-antioxidative status in the rats exposed to Pb. The results suggest that the anti-oxidative properties of sesamin may be one of the underlying mechanisms behind its beneficial effect in ameliorating behavioral deficits associated with Pb exposure.